Market segmentation in B2B service companies - Reyes-Aliaga, Cristobal; Orellana, Eva; Gonzalez-Peña, Tirza; Álvarez, Alejandro; Carrasco, Raúl (EASI: Engineering and Applied Sciences in Industry, 2024)
Industrial market segmentation is a key strategy and challenge for the marketing area. More than 40 years of study and no guidelines have been produced to define strong B2B market segments; There have been few studies that have empirically tested the impact of segmentation. The present study joins previous efforts through a narrative review of the literature, analyzing 25 related articles in B2B marketing. A three-stage investigation is developed consisting of: (1) State of the art of B2B segmentation, (2) The segmentation process in service companies and (3) conclusions about the segmentation process. The cited authors carried out their academic research during the period 1983-2021 and propose expanding the vision of market segmentation of service companies as a continuous process. Services marketers can adopt four activities to segment service markets: (1) presegmentation, (2) segmentation, (3) implementation, and (4) evaluation. Finally, several gaps were identified and a small suggestion for a practice-oriented research agenda is offered.